Randomized Pilot Study: A Mobile Technology-based Self-management Intervention for Sickle Cell Pain. (August 2020) - Ezenwa, Miriam O.; Yao, Yingwei; Nguyen, Minh-Nguyet T.; Mandernach, Molly W.; Hunter, Clayton T.; Yoon, Saunjoo L.; Fedele, David; Lucero, Robert J.; Lyon, Debra; Wilkie, Diana J.
Little is known about the effects of self-managed relaxation interventions on pain, stress, and autonomic responses in patients with sickle cell disease (SCD). This pre-post randomized controlled pilot study was conducted to determine the feasibility of using computer tablets for relaxation intervention delivery; acceptability of study procedures; and intervention effects on pain, stress, and indicators of relaxation. The 30 research participants ranged in age from 22 years to 59 years. All were African American; 53% were male. They were randomized to an experimental group that watched a relaxation video or a control group that discussed their disease. All participants completed the study, indicating feasibility. Acceptability rates were also high. Data were obtained for the intervention's immediate effect on pain, stress, respiration, pulse, finger skin temperature, and self-reported relaxation. These preliminary findings will guide future, higher-powered studies to determine the intervention's efficacy and mechanism in SCD. The ClinicalTrials.gov Identifier: NCT02729363